Deletion of Eqtn in mice reduces male fertility and sperm–egg adhesion. Issue 6 (December 2018) - Ito, Chizuru; Yamatoya, Kenji; Yoshida, Keiichi; Fujimura, Lisa; Sugiyama, Hajime; Suganami, Akiko; Tamura, Yutaka; Hatano, Masahiko; Miyado, Kenji; Toshimori, Kiyotaka
Abstract : A number of sperm proteins are involved in the processes from gamete adhesion to fusion, but the underlying mechanism is still unclear. Here, we established a mouse mutant, the EQUATORIN-knockout (EQTN-KO, Eqtn − / − ) mouse model and found that the EQTN-KO males have reduced fertility and sperm–egg adhesion, while the EQTN-KO females are fertile. Eqtn − / − sperm were normal in morphology and motility. Eqtn − / − - Tg ( Acr-Egfp ) sperm, which were produced as the acrosome reporter by crossing Eqtn − / − with Eqtn +/+ -Tg( Acr-Egfp ) mice, traveled to the oviduct ampulla and penetrated the egg zona pellucida of WT females. However, Eqtn − / − males mated with WT females showed significant reduction in both fertility and the number of sperm attached to the zona-free oocyte. Sperm IZUMO1 and egg CD9 behaved normally in Eqtn − / − sperm when they were fertilized with WT egg. Another acrosomal protein, SPESP1, behaved aberrantly in Eqtn − / − sperm during the acrosome reaction. The fertility impairment of EQTN/SPESP1-double KO males lacking Eqtn and Spesp1 ( Eqtn / Spesp1 − / − ) was more severe compared with that of Eqtn − / − males. Eqtn − / − -Tg ( Eqtn ) males, which were generated to rescue Eqtn − / − males, restored the reduced fertility.